Xenopsylla spp. (Siphonaptera: Pulicidae) in murid rodents from the Canary Islands: An update - Sánchez, S. (EDP Sciences, 2012)
The geographical and host distributions of Xenopsylla fleas parasitizing murid rodents on the Canary Islands have been reported. Three Xenopsylla species, X. cheopis, X. brasiliensis and X. guancha, have been detected on two rodents species, Mus musculus and Rattus rattus. X. guancha has been the most prevalent species detected, specifically on M. musculus, the most abundant rodent, but it has been detected only on three eastern islands, where the species is endemic. X. cheopis has been shown to be the most widely distributed species throughout the archipelago and the species most frequently found on R. rattus. X. brasiliensis has been shown to be the least prevalent Xenopsylla species, with the lowest geographical distribution on the Canary Islands and focused only on R. rattus. The detection of both X. cheopis and X. brasiliensis on the island of Lanzarote, and of X. guancha on the island of Fuerteventura and the islet of La Graciosa represents the first report of these species on those particular Canary Islands.